High-energy ultrafast mid-IR optical parametric amplifier for strong-field science. Issue 8 (January 2020) - Faccialà, D; Musheghyan, M; Geetha, P Prasannan; Pusala, A; Crippa, G; Ciriolo, A G; Devetta, M; Vozzi, C; Stagira, S
Synopsis: We present a high-energy mid-infrared optical parametric amplifier source tunable between 2.8 and 3.8 μ m for strong-field applications. We exploited this source in combination with a 800 nm source for generating high-order harmonics in atoms and molecules in a two-color pulse scheme.